The Importance Of Partnerships With Developing Countries: How To Establish A Microsurgery Course In Kenya - Macarena Vizcay; Juan Enrique Berner; Ferdinand Nangole; Luigi Troisi (Archives of Plastic Surgery)
Surgery is crucial for the advancement of global health as a reduction of the burden of surgically treatable illnesses benefits not only patients quality of life, but also the nations productivity and economic potential. A partnership was established between The University of Nairobi, Kenyatta National Hospital, The Kenyan Society of Plastic, Reconstructive and Aesthetic Surgery, and the The MultiMedica Reconstructive Microsurgery Service to deliver an interactive and hands-on course for plastic surgery trainees based in Nairobi. The aim was to demonstrate complex reconstructions, provide expert advice for the service and inspire the next generation of East African reconstructive plastic surgeons. We believe this will lead to future research and clinical collaborations now that the visiting team has gained knowledge regarding the clinical setup in Nairobi, and the local team have seen what the visiting surgeons can provide from an educational perspective.